Fontes de fósforo e enxofre para cana-de-açúcar - Nicchio, Bruno (2018)
Phosphorus (P) and sulfur (S) have fundamental importance on sugarcane; therefore, the application of these nutrients directly affects the productivity of this crop. Based on that, this study evaluated the performance of phosphorus and sulfur sources in the sugarcane crop. Different sources were evaluated in greenhouse and field experiments. The greenhouse study was conducted on clayey, silty clay and sandy soils. The treatments evaluated were control, TSP, TSP + S0, TSP + Gypsum, MAP + S0, MAP + Gypsum, Reactive Bayovar Phosphate + S0, Reactive Bayovar Phosphate + Gypsum, high reactivity Natural Phosphate + TSP + S0, and low reactivity Natural Phosphate + TSP + S0 (rate of 120 mg kg-1 of P2O5 and 40 mg kg-1 of S). The mixture of phosphate fertilizers and elemental sulfur (S0) was more efficient, increasing dry mass and phosphorus content in the medium texture soil. The low reactivity natural phosphate incorporated with SFT and S0 in the granule and the phosphates mixed with gypsum were more efficient, increasing sulfur accumulated in sugarcane and sulfur contents in clayey soils. The high reactivity natural phosphate incorporated with SFT and S0 in the granule and the phosphates mixed with S0 were more efficient in increasing phosphorus content in sandy soil. The field studies were conducted with application of treatments in the cane planting furrow in two areas, evaluated for two cropping seasons. The treatments evaluated were control, TSP, TSP + S0, TSP + Gypsum, MAP + S0, MAP + Gypsum, Reactive Bayovar Phosphate + S0, Reactive Bayovar Phosphate + Gypsum, high reactivity Natural Phosphate + TSP + S0, and low reactivity Natural Phosphate + TSP + S0 (rate of 120 kg ha-1 of P2O5 and 40 kg ha-1 of S). The mixture of phosphate fertilizers (TSP, MAP and Reactive Bayovar Phosphate) and elemental sulfur was efficient increasing the production of cane tonnage and sugar yield, and the phosphorus levels in the soil. High and low reactivity natural phosphates, both incorporated with SFT and S0 in the granule, were more efficient increasing phosphorus content in the soil than the natural reactive phosphate Bayovar mixed with elemental sulfur and gypsum. The positive effect of gypsum treatments in relation to elemental sulfur may be related to the intensity of the water stress and the conditions of cultivation observed in one of the experiments. Field experiments were also done with different treatments (elemental micronized S, sulfate, thiosulfate, Microessentials® and control). The results of this study showed that S sources containing sulfate and MST (micronized elemental sulfur) were effective in raising leaf S, and stalk S content and accumulation. Cane tonnage and sugar yield of S-treated plots, regardless of source were numerically greater than the control plots for both locations, i.e., St. Gabriel and Donaldsonville. The application of phosphate MST increased BRIX and sucrose content of cane juice at the Donaldsonville site. Moreover, both phosphate MST and Microessentials applications were effective in raising leaf and stalk S content, stalk S accumulation and soil P contents on a silt loam soil.